2018
DOI: 10.1038/s41589-018-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical proteomics reveals new targets of cysteine sulfinic acid reductase

Abstract: Cysteine sulfinic acid or S-sulfinylation is an oxidative post-translational modification (OxiPTM) that is known to be involved in redox-dependent regulation of protein function but has been historically difficult to analyze biochemically. To facilitate the detection of S-sulfinylated proteins, we demonstrate that a clickable, electrophilic diazene probe (DiaAlk) enables capture and site-centric proteomic analysis of this OxiPTM. Using this workflow, we revealed a striking difference between sulfenic acid modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
207
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(215 citation statements)
references
References 59 publications
8
207
0
Order By: Relevance
“…Therefore, the potential implications of these new redox PTMs in histones specially, in histone H3, should be investigated in the near future. Further, other oxidative modifications of the Cys residues (Cys96 and Cys110) of histone H3 such as (S-sulfhydryl persulfide, sulfonamide, sulfonamide, thiosulfinate, or thiosulfate), 59 which account in other proteins should be explored not only by their ability to change the redox state of the thiol group but also by their biological implication in the secondary structure of histone H3 and the quaternary structure of the nucleosome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the potential implications of these new redox PTMs in histones specially, in histone H3, should be investigated in the near future. Further, other oxidative modifications of the Cys residues (Cys96 and Cys110) of histone H3 such as (S-sulfhydryl persulfide, sulfonamide, sulfonamide, thiosulfinate, or thiosulfate), 59 which account in other proteins should be explored not only by their ability to change the redox state of the thiol group but also by their biological implication in the secondary structure of histone H3 and the quaternary structure of the nucleosome.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al described the susceptibility to form sulfenic, sulfinic, and sulfonic acids in Cys96 and Cys110 in the histone variant H3.1, and the formation of sulfonic acid in Cys110 in the histone variant H3.2 in HEK293T cells after oxidative stress . Importantly, Atker et al revealed a striking difference between S‐sulfenylation and S‐sulfinylation dynamic response to oxidative stress, therefore suggesting different roles for these OxiPTMs in redox regulation and signaling . Particularly, S‐sulfinylated proteins appear enriched in diverse biological processes and cellular pathways, including oxidation–reduction, cell–cell adhesion, RNA processing, glycolysis, fatty acids beta‐oxidation, and importantly, protein import into the nucleus .…”
Section: Redox Post‐translational Modifications In Histonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent proteomics experiments have demonstrated that a significant number of proteins exhibit reversible formation of cysteine sulfinic acids, indicating that cysteine sulfinic acid is a widely distributed protein posttranslational modification responsive to oxidative conditions or signaling . Oxidation of cysteine to the sulfinic acid can induce activating or inhibiting functional changes to proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Given the broad range of proteins whose functions might be regulated by Cys oxidation to the sulfinic acid, we and others have sought to develop new ways to interrogate this oxidation state of cysteine. Recently, a number of molecular probes that react specifically with Cys sulfinic acid have been developed . These bioconjugation reagents take advantage of the nucleophilic character of Cys sulfinic acid.…”
Section: Introductionmentioning
confidence: 99%